Equality and Survivability: COVID-19 and Persons with Disability in Malaysia - Teoh Jia Long; Muhammad Idris Bullare @ Bahari; Fariz A. Rani (Psychology and Social Health Research Unit, 2023)
Many have become victims of the COVID-19 pandemic, and the virus has changed how we live our lives significantly. In order to mitigate the spread of the virus, various countries have implemented non-pharmaceutical approaches such as spatial distancing and partial lockdown. Be that as it may, the strong countermeasure applied poses several issues towards persons with disabilities (PWDs) due to their limitations in mobility, as well as a country’s poor policy planning. This paper sought to discuss some of the issues experienced by PWDs in Malaysia during the COVID-19 pandemic as well as some relevant suggestions.